PELAYANAN PUBLIK DALAM PENANGANAN SAMPAH DI KOTA PEKANBARU TAHUN 2019-2020 - Endah Wulandari; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The waste problem has indeed become a frightening specter for the City of Pekanbaru, so this has made the Pekanbaru City Government and legislature stifled, even several times the DLHK Kota Pekanbaru has often been criticized for their performance in handling waste in Pekanbaru. The performance of cleaning staff is not yet effective and efficient in carrying out their responsibilities so that the growth in the amount of waste in Pekanbaru City continues to increase sharply every year. The limited trash collection is also one of the special highlights in Pekanbaru City. The high flow of urbanization causes Pekanbaru City to always experience an increase in population, which is the main reason for the increasing amount of waste complexity. This study aims to analyze public services in handling waste in Pekanbaru City and all efforts, both services and programs, and performance to overcome this waste problem. The theory used in this study is based on the dimensions of service quality from Zeithaml, divided into five dimensions including Tangibles, Reliability, Responsiveness, Assurance, Empathy. The research method used in this study is a qualitative research method. Data collection techniques through interviews, observation, and documentation studies from several sources. The results of this study show that by using five dimensions to measure the quality of waste handling services in Pekanbaru City, along with the quality of waste handling services in Pekanbaru City, they are still not going well. There are dimensions that have been considered quite good, namely the Responsiveness dimension, and the Empathy dimension. However, there are still dimensions of service quality that need attention and improvement, namely the Tangibles dimension, the Reliability dimension, as well as the Assurance dimension. Several factors influence the effectiveness of waste management by the DLHK Kota Pekanbaru, namely human resources, community awareness, and facilities and infrastructure. Keywords: Public Service, Waste Handling, Local Government